Control of bacterial biofilms in red meat – A systematic review. (October 2022) - Rahman, S.M.E.; Islam, S.M.A.; Xi, Qian; Han, Rongwei; Oh, Deog-Hwan; Wang, Jun
Abstract: Biofilm formation is a serious threat in the meat industry, mainly since it aids food-borne pathogen survival. Biofilms are often difficult to eliminate, and it is essential to understand the best possible deployable measures to remove or inactivate biofilms. We systematically reviewed the published in vitro studies that investigated various methods for removing biofilms in red meat. Publicly available databases, including Google Scholar and PubMed, were queried for relevant studies. The search was restricted to articles published in the English language from 2010 to 2021. We mined a total of 394 studies, of which 12 articles were included in this review. In summary, the studies demonstrated the inhibitory effect of various methods, including the use of bacteriophages, dry heat, cold atmospheric pressure, ozone gas, oils, and acids, on red meat extract or red meat culture. This systematic review suggests that in addition to existing sanitation and antibiotic procedures, other methods, such as the use of phage cocktails and different oils as nanoparticles, yield positive outcomes and may be taken from the in vitro setting to industry with prior validation of the techniques. Highlights: Red meat production and process may involve various pathogenic and spoilage microbes. Most of these microbes were able to form biofilms. We systematically reviewed the in vitro studies that imply novel techniques against the biofilms production, formation or activation in red meat. Phage cocktail and different oils as nano particles may be useful for industrial applications.